2013
DOI: 10.1074/jbc.m112.449348
|View full text |Cite
|
Sign up to set email alerts
|

An Antedrug of the CXCL12 Neutraligand Blocks Experimental Allergic Asthma without Systemic Effect in Mice

Abstract: Background: The chemokine CXCL12 and its receptor CXCR4 are widely distributed and contribute to the physiopathology of inflammation.Results: Recruitment of eosinophils in the inflamed airway is selectively attenuated by short lived antagonists that block CXCL12-mediated activation of CXCR4.Conclusion: CXCL12/CXCR4 signaling regulates local leukocyte-mediated inflammation.Significance: Antedrugs of neutraligands allow dissecting the physiological role of chemokines, especially when expression occurs in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 67 publications
2
37
0
Order By: Relevance
“…The use of neutraligands is a very interesting therapeutic strategy because they do not bind the chemokine receptors and thereby do not modify cell homeostasis [21, 23]. We recently described the anti-inflammatory activity of chalcone 4 in a murine model of allergic airway hypereosinophilia [6, 14, 15]. The present study confirmed the anti-inflammatory effect of chalcone 4 treatment in asthma, with decreased numbers of inflammatory cells in BALF.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The use of neutraligands is a very interesting therapeutic strategy because they do not bind the chemokine receptors and thereby do not modify cell homeostasis [21, 23]. We recently described the anti-inflammatory activity of chalcone 4 in a murine model of allergic airway hypereosinophilia [6, 14, 15]. The present study confirmed the anti-inflammatory effect of chalcone 4 treatment in asthma, with decreased numbers of inflammatory cells in BALF.…”
Section: Discussionsupporting
confidence: 72%
“…Chalcone 4 was therefore called a neutraligand. Administered intranasally, chalcone 4 decreased the recruitment of inflammatory cells, in particular eosinophils, in a mouse model of allergic eosinophilic airway inflammation [6, 14]. Furthermore, chalcone 4 derivatives, modified as highly soluble prodrugs, attenuated at very low doses the inflammatory reaction in an allergic airway hypereosinophilia model [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that inhibition of CXCL12/CXCR4 signaling attenuated allergic lung inflammation and AHR (5,6,23). However, the exact underlying mechanisms have yet to be fully understood.…”
Section: A B C D Discussionmentioning
confidence: 99%
“…CXCL12 binds to chemokine (C-X-C motif) receptor 4 (CXCR4) and attracts a variety of cells, including resting T lymphocytes, monocytes, CD34 + stem cells and mature eosinophils (3). CXCL12 and its receptor CXCR4 have been demonstrated to be involved in Th2-type allergic airway responses, and inhibition of CXCL12 or CXCR4 leads to reduced airway inflammation and AHR (4)(5)(6). Furthermore, another study demonstrated that the levels of CXCL12 were significantly higher in bronchoalveolar lavage fluids (BALF) of asthmatic patients compared with healthy individuals, and the concentration of CXCL12 was correlated with inflammatory cell numbers in the BALF (7).…”
Section: Introductionmentioning
confidence: 99%